Violating Maxims, Preserving Harmony: Pragmatic Strategies in Arabic Humor on Instagram Reels - Ka'bal Umam, Deden (ELS Journal on Interdisciplinary Studies in Humanities, 2024)
Humor plays a vital role in human communication, serving complex social functions, especially within the Arab cultural context. This study aims to analyze the pragmatic aspects of Arabic humor by examining violations of cooperative principles and politeness strategies found in humorous dialogues. It focuses on pragmatic analysis based on Grice's cooperative principle and Brown and Levinson's politeness theory. These theoretical frameworks are particularly relevant to Arabic humor given the culture's strong emphasis on indirect communication and face-saving practices in social interactions. Using a qualitative descriptive approach, the research analyzes ten humorous dialogues from Instagram Reels shared by the user @taraef_alarab. The study reveals that Arabic humor's effectiveness often lies in the intentional violation of the maxims of relation and quantity, along with the sophisticated use of politeness strategies to navigate sensitive situations, particularly within family and marital contexts. These findings confirm that humor serves as a social mechanism, allowing for the discussion of sensitive topics in a culturally acceptable manner. This research contributes to a deeper understanding of the pragmatic role of humor in intercultural communication and provides an analytical framework for studying humor within the Arab socio-cultural context.